DIGITAL VAGINAL EXAMINATION VS TRANSABDOMINAL ULTRASOUND ASSESSMENT TO DIAGNOSE MALPOSITION BEFORE ATTEMPTING INSTRUMENTAL VAGINAL DELIVERY – WHICH IS A BETTER TOOL - Ghazala Huma; Asifa Siraj; Viqar un Nisa; Ayesha Imran; Umairah Yaqub; Khichi, Rabia Qasim (Journal of Ayub Medical College Abbottabad, 2025)
Background: Fetal malposition play a vital role in the progress of labor and correct identification of the fetal position may impact the mode of delivery. The main purpose of this comparative cross-sectional study is to diagnose fetal malposition on vaginal versus ultrasound examination before attempting instrumental vaginal delivery at a tertiary care hospital setting in Pakistan. Place and Duration: Gynaecology and Obstetrics department Tertiary care hospital, Pakistan. August 2023 - January 2024. Methods: Pregnant females with singleton pregnancy of any age group without any previous history of systemic disease, booked cases with an indication of operative vaginal delivery were included in the study. Using non-probability consecutive sampling technique Group-V (n=72) patients underwent a digital vaginal exam however Group-U (n=72) underwent ultrasound trans-abdomen during the second stage of labor. The position of the fetus on a digital vaginal exam (DVE), and transabdominal ultrasound was recorded. Visual identification of the occiput position was recorded and considered the gold standard. Results: Median (IQR) age in years was 30.5(28-32). The recorded BMI of the participants was 28(26-30) Kg/m2 and most of these pregnant patients had parity 2. The median time taken to perform the exam in seconds was 16(15-18.5) in Group-V as compared to 35 (32–38) in Group-U (p-value<0.001). Occiput anterior including (OA, LOA, and ROA) were the most common fetal positions observed in both groups. The DVE was able to correctly identify the fetal position in 54(75%) patients as compared to 67(93.1%) correct findings after the ultrasound exam with a p-value of 0.003. Conclusion: Transabdominal ultrasound is a more reliable modality as compared to digital vaginal examination in identifying fetal malposition before instrumental vaginal delivery.